Fluorinated Adenosine A2A Receptor Antagonists Inspired by Preladenant as Potential Cancer Immunotherapeutics. (19th October 2017) - Yuan, Gengyang; Jankins, Tanner C.; Patrick, Christopher G.; Philbrook, Phaethon; Sears, Olivia; Hatfield, Stephen; Sitkovsky, Michail; Vasdev, Neil; Liang, Steven H.; Ondrechen, Mary Jo; Pollastri, Michael P.; Jones, Graham B.
Abstract : Antagonism of the adenosineA 2 A receptor on T cells blocks the hypoxia-adenosinergic pathway to promote tumor rejection. Using an in vivo immunoassay based on the Concanavalin A mouse model, a series ofA 2 A antagonists were studied and identified preladenant as a potent lead compound for development. Molecular modeling was employed to assist drug design and subsequent synthesis of analogs and those of tozadenant, including fluorinated polyethylene glycol PEGylated derivatives. The efficacy of the analogs was evaluated using two in vitro functional bioassays, and compound29, a fluorinated triethylene glycol derivative of preladenant, was confirmed as a potential immunotherapeutic agent.